Use of Cattle Rumen Fluid in Moringa Leaf Flour Fermentation (Moringa oleifera l.) to Improve the Performance of Laying Quail (Coturnix coturnix japonica) - Lumbantobing, Anggyana Faith; Nurjama’yah Br. Ketaren; Sayed Umar (Jurnal Peternakan Integratif, 2024)
Moringa leaf flour is a plant that contains good nutrients and high antinutrients. One of the efforts to degrade crude fiber and detoxify antinutrients through fermentation with cattle rumen fluid. This research aims to determine the effect of fermented Moringa leaf flour with cattle rumen fluid on feed consumption, body weight gain, feed conversion female quail grower phase, and age at first egg-laying. This research was held at the Livestock laboratory of Animal Science Study Program, Faculty of Agriculture, Universitas Sumatera Utara, from February to March 2024. The design experiment used a completely randomized design with 4 treatments and 5 replications, where each plot contained 5 female quails. Treatment were consisted of T0 (100% commercial feed), T1 (96% commercial feed + 4% fermented moringa leaf flour), T2 (92% commercial feed + 8% fermented moringa leaf flour) and T3 (88% commercial feed + 12% fermented moringa leaf flour). The results showed that the effect of using fermented moringa flour with cattle rumen fluid mixed with commercial feed was able to affect the performance of laying quail, with the best treatment is T2 (92% commercial feed + 8% fermented moringa leaf flour).